Price Variation of Injectable Antibiotics Commonly used in Bharatpur, Chitwan - Sah, Ajit Kumar; Giri, Anish; Palikhey, Anjan; Chaurasiya, Roshan Kumar; Sah, Phoolgen; Mallik, Mukesh (Journal of Gandaki Medical College-Nepal, 2021)
Introduction: High dispersion in price of injectable antibiotics makes choice of drugs difficult for the patients and increase economic burden. Thus, objective of this study is to find outrange of price variation of injectable antibiotics commonly used in Bharatpur, Chitwan. Methods: Descriptive observational study of 30 commonly used injectable antibiotics available in medical stores of Bharatpur, Chitwan was done. Range in price variation of the study items of different pharmaceutical companies was calculated in terms of price percentage difference and price ratio by selecting the highest and lowest price. The effect of rise in number of companies for the same drugs over the prices was also studied subjectively based upon graph. Results: We found that the price percentage difference was greatest (204.82%) for Ceftriaxone 500 mg. The maximum retail price (MRP) of the most expensive brand for Ceftriaxone 500 mg was almost three-fold higher than the MRP of the least expensive brand. The growing number of companies also increased dispersion in the price of drugs. Conclusions: There is wide range of price variation of injectable antibiotic commonly used in the Bharatpur, Chitwan. Increasing number of companies in the market has further widened the range. Policy to regulate the price of injectable antibiotic is needed.